How why how do we do anything means everything - Seidman, Dov. (2007 John Wiley & Sons)
The flood of information and unprecedented transparency reshaping today?s business world has dramatically changed the rules of the game. It?s no longer what you do that sets you apart from others, but how you do what you do. Whats are commodities, easily duplicated or reverse-engineered. Sustainable advantage and enduring success?for both companies and the people who work for them?now lie in the realm of how, the new frontier of conduct. For more than a decade, Dov Seidman?s pioneering organization, LRN, has helped some of the world?s most respected companies build "do it right," winning cultures. Seidman?s distinct vision of the world, business, and human endeavor has enabled more than ten million people doing business in over 100 countries to outbehave the competition. In HOW: Why How We Do Anything Means Everything . . . in Business (and in Life), Dov Seidman shares his unique approach with you. Through entertaining anecdotes, surprising case studies, cutting-edge research in a wide range of fields, and revealing interviews with a diverse group of business leaders, experts, and everyday people on the front lines, this book explores how we think, how we behave, and how we govern ourselves to uncover the values-driven "hows" of 21st-century success.
Includes bibliographical references (p. 325-330) and index.
Keywords: Success in business